Recovery of the Hypothalamic-Pituitary-Testicular Axis After Anabolic-Androgenic Steroid Cessation. A Review of Therapeutic Options and the Fundamental Role of the Primary Care Physician in Harm Reduction. - Rzeszutek, Jakub; Pempuś, Wiktoria; Grzybowska, Dominika; Niderla, Natalia; Rachwał, Natalia; Grzyb, Weronika; Kurnik, Michał; Jaślikowska, Adrianna; Idzik, Kamil; Kubicki, Adrian (Quality in Sport, 2026)
The recreational abuse of anabolic-androgenic steroids (AAS) is a major public health concern among amateur athletes. Supraphysiologic androgen exposure disrupts the hypothalamic-pituitary-testicular axis, inducing Anabolic Steroid-Induced Hypogonadism (ASIH). This study evaluates endocrine and spermatogenesis recovery timelines, reviews pharmacological interventions, and defines the role of primary care physicians (PCPs) in harm reduction. Based on a comprehensive literature review from 1990 to 2025, twenty key publications were analyzed. Results indicate that spontaneous axis recovery is prolonged. While serum testosterone normalizes within 3 months post-cessation, full spermatogenesis recovery averages 12 months. Up to 27 percent of former users exhibit persistent hypogonadism and psychiatric withdrawal symptoms years later. Combined off-label pharmacotherapy using human chorionic gonadotropin (hCG) alongside selective estrogen receptor modulators (SERMs) accelerates testosterone restitution and restores fertility in over 70 percent of azoospermic patients. General practitioners occupy the critical frontline to mitigate life-threatening complications through clinical surveillance.